Microplastic ingestion and retention in penaeid shrimp from the Arabian Sea - Sancia Morris; Pathissery John Sarlin; Sandie Morris; Polycarp Joseph (Discover Environment)
Abstract Microplastics (MPs) pollution has become a significant environmental concern globally, with emerging evidence indicating their widespread presence in marine ecosystems. Among the diverse range of aquatic organisms affected by MPs, shrimp occupy a crucial ecological niche and serve as a valuable food source for marine predators and human consumption. This study reports MP content in the gastrointestinal tracts of four species of commercially important penaeid shrimps—Fenneropenaeus indicus, Penaeus monodon, Penaeus semisulcatus and Metapenaeus affinis from the marine waters of Kerala, India. The gastrointestinal tract of shrimps was examined for MPs following alkali digestion, microscopic observation, and chemical analysis using ATR FTIR and Raman Spectrum Analysis. A total of 108, 74, 125 and 382 MP items were found in F. indicus, P. monodon, P. semisulcatus and M. affinis averaging 1.08 ± 2, 0.74 ± 2, 1.25 ± 2 and 1.91 ± 2 items/species, respectively. Among the various shapes fibre (31.8%), pellet (32.4%), sphere (33.38%) and fragment (2.47%) were present. Different colours of MPs such as black, blue, red, and transparent were identified. The ATR FTIR data confirmed the presence of 16 particles of polyethylene, 14 of polyvinyl chloride, 9 of nylon 66, 10 of acrylonitrile butadiene styrene (ABS), 11 of polystyrene and 9 non-plastic particles. These results provide baseline data of MP contamination in commercially important penaeid shrimps from Kerala, which should be useful for future monitoring efforts.